The Effect of Chicken Manure and SNN (Super Natural Nutrition) Liquid Organic Fertilizer Application on Sweet Corn Growth and Production (Zea mays L. saccaharata Sturt) - Saragih, Meylin Kristina; Simanjuntak, Pantas; Panataria, Lince Romauli; Sitorus, Efbertias (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to determine the effect of applying chicken manure and liquid organic fertilizer.SNN(super natural nutrition) on the growth and production of corn plants (Zea mays saccharata Sturt). This study used a Factorial Randomized Block Design (RAK) with two factors. The first factor is Liquid Organic FertilizerSNNconsists of 3 (three) levels: S0 = Control, S1 = 3 ml/l of water per plot, and S2 = 5 ml/l of water per plot. The second factor is chicken manure consisting of 4 (four) levels: A1 = 1 kg/plot (7 tons/ha), A2 = 1.5 kg/plot (10 tons/ha), A3 = 2 kg/plot (13 tons/ha) and A4 = 2.5 kg/plot (16.5 tons/ha). The study's results showed that the treatment of liquid organic fertilizers 5 ml/l of water per plot significantly affected plant height, stem diameter, and weight of cob with husk per plant. Chicken manure 2.5 kg/plot had no significant effect on plant height, stem diameter, or weight of cobs with husks per plant. Interaction between liquid organic fertilizer and chicken manure sometimes had no significant effect on all observed parameters.